2014
DOI: 10.1080/10934529.2014.893795
|View full text |Cite
|
Sign up to set email alerts
|

Removal of particles in organic filters in experimental treatment systems for domestic wastewater and black water

Abstract: This study assesses the total suspended solids (TSS) retention capacity of different organic filter media for two potential applications: (i) a polishing unit for package treatment plants and (ii) a pretreatment for blackwater from low-flushing toilets. The results showed that the peat filter media used can be significantly improved in terms of structural stability and TSS removal capacity by mixing it with sawdust. Most of the TSS accumulated in the upper part of the filter material, and filter thickness exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…These results have provided the wastewater standards discharge values (e-Legislation no: 7221). Similar results have been reported elsewhere (Todt et al 2014;Karpuzcu et al 2020). Chun et al (2008) found that the influent water SS concentration was 184 mg/L, while the effluent water SS concentration was 6-17 mg/L.…”
Section: Resultssupporting
confidence: 90%
“…These results have provided the wastewater standards discharge values (e-Legislation no: 7221). Similar results have been reported elsewhere (Todt et al 2014;Karpuzcu et al 2020). Chun et al (2008) found that the influent water SS concentration was 184 mg/L, while the effluent water SS concentration was 6-17 mg/L.…”
Section: Resultssupporting
confidence: 90%
“…In a filtration process, not only could suspended solids (SS) be removed to decrease the subsequent treatment loads and avoid system blockage, but attachment of pathogens or shedding of disinfectants could also be disturbed (Pype et al, 2016). Filters that have been reported include peat and sawdust (Todt et al, 2014), sand and nonwoven textile (Tao et al, 2011), activated carbon (Sahondo et al, 2020) and more commonly, membranes (van Voorthuizen et al, 2005;van Voorthuizen et al, 2008;Kamranvand et al, 2020). The application of organic percolation filters is limited due to the severe clogging .…”
Section: Treatment Technologies Of Blackwatermentioning
confidence: 99%
“…The application of organic percolation filters is limited due to the severe clogging . A novel mechanical filter device combining traditional screening with a new type of counterflow filter using an organic media was therefore developed by Todt et al (2014) and applied in mountain cabins. They reported the employment of a mixing filter composed of peat and sawdust to the treatment of settled BW, and a TSS reduction of 60%-75% was achieved.…”
Section: Treatment Technologies Of Blackwatermentioning
confidence: 99%
“…By comparing the effect of filter height on SS removal, Todt et al, (2014) indicated that most of the filtration process took place in the uppermost part of the filter (15 cm). Considering the configuration of the SSTS used in our study, greywater can easily flow through the entire filter length so that, an increase in filter length will enhance the organic matter removal performance.…”
Section: Influence Of the Pilots Configurations On The Treatment Efficiencymentioning
confidence: 99%